BATAS MAKSIMAL HAK MOGOK KERJA BERDASARKAN UNDANG-UNDANG NO 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Evangeline Fiona; Gunardi Lie (Fakultas Hukum Universitas Tarumanagara, 2021)
The working strike is the basic right of worker. Therefore, everyone can not stop implementing his right. If anyone is against this regulation, so can be punished.This right is implemented in according to regulation specially UU Nomor 13 Tahun 2003 and Kepmenakertrans Nomor: Kep-232/Men/2003 in order to evaluate as a legal working strike.The working stike can only be implemented at the certain factory, and there are no time’s regulation to implement working strike. A strike is a fundamental right held by workers and a labor union/labor union. This right of strike is clearly set out in Article 137 Employment Security Act (Act No. 13 of 2003). go on strikea cannot be done freely, there are limits and provisions that sayhis attraction, the act of lawfully, orderly, and peacefully as a result of its failure a negotiation. But in some cases, there are still frequent acts of mogok work that is done legitimately, but is considered to be in violation of regulation yang take effect because of the unfulfillment of the conditions for going on strike.then what are the criteria for a strike to be carried out by workers/workers so that para the worker/worker may exercise his/her rights and obtain legal guarantees.